Legitimacy of International Intervention in the Internal Affairs of States Under the Pretext of Combating Terrorism After the Events of September 11, 2001 (Damascus University Journal for the economic and Political sciences, 2025)
Fighting terrorism, whether on a domestic or international scale, is one of the most important responsibilities placed on the entire international community—both countries and organizations—due to the threat it poses to international peace and security. In the context of the declared campaign against international terrorism, there has been a debate about the relationship between global counterterrorism efforts and international law principles concerning states and the UN Charter, such as the principles of sovereignty and non-intervention, especially after the September 11 attacks in 2001. Recognizing the independence and sovereignty of states is one of the fundamental conditions established by international law practices and the UN Charter, which prohibits the use of force in international relations.Counterterrorism efforts can lead to changes in the rules of international law that govern state relationships, especially since they are based on the principles outlined in Article 2 of the UN Charter. This idea has begun to take shape in the declared campaigns against terrorism, which involve the use of force under the authority of the Security Council, in addition to the right of self-defense provided for in Article 51 of the Charter.
Keywords: International Counter-Terrorism; Principles of International Law; Right of Legitimate Self-Defense; Article 51 of the United Nations Charter